Abiotic Regulation: Landslide Scale and Altitude Regulate Functional Traits of Regenerating Plant Communities After Earthquakes - Kang, Di; Zou, Shuzhen; Ma, Long; Yin, Caijia; Zhu, Dahai (Frontiers in Ecology and Evolution, 2022)
Regeneration and assembly of a plant community after a large-scale natural disturbance are affected by many factors. The relative importance of abiotic factors represented by the external environment and the biological factors inside the plant community during this process is still unexplored. This work investigated the regions affected by the Wenchuan earthquake, focusing on areas with the highest intensity (XI degrees) of this earthquake, and the process of community assembly through functional traits on landslides. The aim of this study was to understand the importance of factors influencing community assembly from the perspective of functional traits. The main conclusion is presented as follows: after the regeneration of large earthquake-induced landslides, community-level functional traits covering many plant organs, such as roots, stems, leaves and seeds, are obviously different from those unaffected by landslides. Functional traits do not show strong phylogenetic conservatism. Overall, community traits are divergent or random, and the degree of divergence among the different traits varies. Species composition and alpha diversity have minimal effect on community functional traits during the process of landslide restoration. Landslide scale and altitude significantly affected community-level functional traits in the process of community assembly. All the findings suggested that the functional traits of regenerating vegetation after the earthquake changed significantly and that the functional traits depended more on abiotic regulation than on evolutionary and species-specific factors.